Chrám Matky božej v Paríži - Hugo, Victor; Bartko, Michal; Mrlian, ondrej; Stanislav, Ivan (Bratislava Slovenský spisovateľ, 1963)
Klasický príbeh vášnivej lásky a nenávisti...
Povinná literatúra
Keywords: HISTORICKE ROMANY